Studi Geologi Daerah Titidu Kecamatan Kwandang Kabupaten Gorontalo Utara - Wangi, Akrein Vender; Permana, Aang Panji; Zainuri, Ahmad (Journal of Applied Geoscience and Engineering, 2024)
The research location is in the Titidu area, North Gorontalo Regency. This study aims to determine the distribution of volcanic igneous rocks in the Titidu area. The research method used in this study is surface geological mapping to determine the geology of the research area, and for data processing using petrographic analysis. The results of the study found that the geomorphology of the research area is volcanic hills, structural hills and alluvial plains, the stratigraphy of the research area is sorted from old to young is an altered andesite unit, andesite unit, pyroclastic breccia unit and fluvial sediment unit. The geological structure in the research area is in the form of a fracture (tension joint) with a general direction of northeast - southwest. Based on the results of petrography, the type of rock is basaltic andesite.